Simulation and Real Time Implementation of Various PWM Strategies for 3 Φ Multilevel Inverter Using FPGA - C. R. Balamurugan; S. P. Natarajan; T. S. Anandhi; B. Shanthi (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
For high power applications Multilevel Inverter (MLI) is extensively used. The major advantages of MLI are good power quality, low switching losses and maintenance of the desired voltage. In this work, the three phase cascaded multi level inverter is analyzed under various modulation techniques that include Sub-Harmonic Pulse Width Modulation (SHPWM) i.e. Phase Disposition (PD) strategy, Phase Opposition Disposition (POD) strategy, Alternate Phase Opposition Disposition (APOD) strategy, hybrid strategy (PD and PS) and Phase Shift (PS) strategy. The study will help to choose those techniques with reduced harmonics for the chosen three phase cascaded MLI with R-L load. The Total Harmonic Distortion (THD), VRMS (fundamental), crest factor and form factor are evaluated for various modulation indices at two different switching frequencies (3.15KHz and 6 KHz). Simulation is performed using MATLAB-SIMULINK. It is observed that HYBRID PWM and PSPWM methods provide output with relatively low distortion for low and high switching frequencies. PODPWM and PSPWM are found to perform better since they provide relatively higher fundamental RMS output voltage for 6 KHz and 3.15 KHz switching frequencies. The experimental result shows PSPWM provide output with low distortion and HYBRID PWM provide output with higher fundamental RMS voltage for fc=3.15KHz. The experimental results were obtained only for fc=3.15KHz.